Does Religious Commitment Mediate the Association Between Acculturative Stress and Latinx Young Adults’ Tobacco Use? - Hernández Dubon, Rafael E. (Journal of cross-cultural psychology, 2022)
Tobacco use is a public health priority in the Latinx community. Identifying factors associated with less tobacco use could help inform community-based prevention efforts. The present study examined whether religious commitment (intrapersonal and interpersonal) mediated the association between acculturative stress and tobacco use among 224 Latinx young adults. Participants completed a battery of measures that included cultural stressors, religious commitment, and tobacco use. Controlling for age and gender, mediation analyses revealed a significant indirect effect in that acculturative stress predicted greater intrapersonal religious commitment, which in turn predicted less tobacco use. There was no direct relationship between acculturative stress and tobacco use. Interpersonal religious commitment was negatively related to tobacco use, but did not mediate the association between acculturative stress and tobacco use. Findings support the need for initiatives to decrease tobacco use among Latinx young adults that include a focus on intrapersonal religious commitment in response to acculturative stress.